Palynoflora from the La Anita Formation (Maastrichtian), Austral-Magallanes Basin, Argentina - Santamarina, Patricio Emmanuel (2020)
Here we describe the spore and pollen assemblages recovered from the La Anita Formation, Late Cretaceous, Austral-Magallanes Basin (~50°S). This unit shows a high diversity of spores, with subordinate gymnosperms (mainly represented by Podocarpaceae) and angiosperms (mainly represented by Proteaceae and Arecaceae). The abundance of these groups varies between the two fertile studied levels, being one dominated by ferns (mainly Cyathidites minor and Laevigatosporites ovatus) and the other by gymnosperms (Podocarpidites spp.). The presence of aquatic ferns (Azollopsis), diverse Podocarpaceae and key angiosperm taxa (such as Arecipites, Clavatipollenites, Dichastopollenites, and Spinizonocolpites) is indicative of warm and hyper-humid conditions. The great abundance of Arecaceae and the presence of some key taxa (e.g. Azollopsis sp., Ericipites scabratus, Peninsulapollis gillii, Proteacidites spp.) support a probable Maastrichtian age for the uppermost strata of the La Anita Formation. The multivariate statistical analysis here conducted showed that the La Anita Formation has its greatest similarity with the La Irene Formation (Maastrichtian from the Austral-Magallanes Basin). Both formations are also related with other coeval palynofloras from Patagonia and Antarctica.